Inhibition of Maternal-to-Fetal Transfer of IgG Antibodies by FcRn Blockade in a Mouse Model of Arthrogryposis Multiplex Congenita. Issue 4 (July 2021) - Coutinho, Ester; Jacobson, Leslie; Shock, Anthony; Smith, Bryan; Vernon, Anthony; Vincent, Angela
Abstract : Objective: To determine whether blocking the neonatal Fc receptor (FcRn) during gestation with an anti-FcRn monoclonal antibody (mAb) reduces transfer of pathogenic maternal antibodies in utero and decreases the likelihood of maternal antibody-mediated neonatal disease in the offspring. Methods: Using a previously established maternal-to-fetal transfer mouse model of arthrogryposis multiplex congenita (AMC), we assessed the effect of 4470, an anti-FcRn mAb, on the transfer of total human immunoglobulin G (IgG) and specific acetylcholine receptor (AChR)-antibodies from mother to fetus, as well as its effect on the prevention of neurodevelopmental abnormalities in the offspring. Results: Offspring of pregnant dams treated with 4470 during gestation showed a substantial reduction in total human IgG and AChR antibody levels compared with those treated with the isotype mAb control. Treatment with 4470 was also associated with a significant reduction in AMC-IgG–induced deformities (limb or spinal curve malformations) when compared with mAb control–exposed embryos and a nonsignificant increase in the percentage of fetuses showing spontaneous movements. 4470 exposure during pregnancy was not associated with changes in general parameters of maternal well-being or fetal development; indeed, male neonates showed faster weight gain and shorter time to reach developmental milestones. Conclusions: FcRn blockade is a promising therapeutic strategy to prevent the occurrence of AMC and other human maternal autoantibody-related diseases in the offspring.